Pengaruh Pemanfaatan Media Pembelajaran E-Learning Terhadap Motivasi Belajar Mahasiswa Pendidikan Ekonomi Universitas Muhammadiyah Bengkulu - Suharmi Suharmi; Dhita Aviani (Universitas Dehasen Bengkulu, 2022)
This study aims to (1) determine the use of e-learning learning media for Economic Education students at Muhammadiyah University of Bengkulu. (2) to find out the learning motivation of Economic Education students at the University of Muhammadiyah Bengkulu. (3) to find out how much influence the use of E-Learning media has on the learning motivation of Economic Education students at Muhammadiyah Bengkulu University. The method used in this research is quantitative by using statistical analysis simple linear regression test. Data collection techniques in the form of observation, questionnaires and documentation. The population in this study were students of Economic Education, Muhammadiyah University of Bengkulu, with a sample of 58 students of Muhammadiyah University of Bengkulu. The sampling technique used is the layered random technique. The results of this study indicate that: (1) Utilization of e-learning learning media with an average value of 58 in the good category, namely in the interval range (52-63). (2) Students' motivation to study at the University of Muhammadiyah Bengkulu with an average score of 62 in the good category, namely in the interval range (52-63). (3) There is a significant effect of the use of E-Learning learning media on the Learning Motivation of Economic Education Students at Muhammadiyah University of Bengkulu with the regression equation Y = 37.16 + 0.43 X this is obtained from the results of the f arithmetic value 9.73> f table 4 .01 and the level of influence is 9%..